Dynamic parameter identification of cold-formed storage rack systems using shaking table test - AL-Gaadi, Fuad M. A.; Alemdar, Fatih (ELSEVIER, 2024)
In this paper, 1:3 scale shaking table tests were performed on three cold-formed steel rack systems with three levels of different heights at the structural laboratory, Yildiz Technical University, to evaluate the factors that affect the dynamic characteristics of the rack systems that are exposed to different excitation frequencies representing the ground motion. The experiments were conducted using a small shaking table designed for this purpose. The dynamic characteristics of the racks were predicted with the help of the signal processing toolbox in MATLAB using the test output data. The results demonstrated that as the mass of the rack structure increases, the rack system vibration frequency caused by external excitation decreases. Also, the damping ratio of the rack systems increases with an increase in the rack height due to the increase in stiffness, and then it starts decreasing because the structure's stiffness begins to decrease with long-term vibration. The modal analysis results demonstrated that the peak-picking (PP) method outperformed the least-squares complex exponential (LSCE) and least-squares rational function estimation (LSRF) approaches in damping estimation. However, each approach achieved nearly identical results for the response frequency in the same mode.
Keywords: Shaking table test; Cold-formed rack systems; Dynamic parameters estimation; Modal identification test; Modal analysis; ONLINE IDENTIFICATION; SEISMIC RESPONSE; DAMAGE DETECTION; VIBRATION; FRAMES; Engineering